An analysis of temporal relations in languages: a comparative study of Mandarin and isiXhosa - Ma, Xiujie (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2013)
This study sought to investigate how temporal relations are expressed in Mandarin and isiXhosa. The objective was to compare how two typologically distinct languages, one isolating and the other agglutinating, cope with the encoding of situations that occur at different positions on the time line. Data was drawn from questionnaire responses from, and interviews with, isiXhosa speakers who provided translations of a wide range of sentences from English into isiXhosa. The study revealed that isiXhosa relies on the grammatical category "“ tense "“ to encode temporal relations, while Mandarin relies more on lexical and pragmatic devices "“ the use of temporal adverbials and the implication of aspectual markings "“ to locate a situation on the time line. Typically, each sentence in isiXhosa must be marked for tense: temporal adverbials are optional elements and used to more precisely locate the situation on the time line. By contrast, in Mandarin, temporal adverbials have a more central function in that they independently express different positions on the time line: without temporal adverbials, it is extremely difficult to locate a situation on the time line in some sentences. Another important difference between the two languages was revealed in this study: isiXhosa grammar allows speakers to talk about situations in terms of their distance (past or future) from the speech time whereas Mandarin grammar allows its speakers to talk about situations in terms of the internal properties (e.g. completed, ongoing, etc.) of those situations. The study revealed that isiXhosa and Mandarin are similar in one important respect: both languages have no formal properties, i.e. overt tense markers (isiXhosa) and compulsory temporal adverbials or other temporal devices (Mandarin) for marking the temporal location of present situations. The study also revealed that both languages encode 'pastness' in terms of whether or not the effects of the situation in question still remain at speech time.
Keywords: Chinese language; Xhosa language -- Grammar, Comparative and general -- Temporal constructions